(untitled) (Comparative & International Education Series, 2021)
As the COVID-19 pandemic forced universities across the US to abruptly transition into remote teaching, instructors and students alike struggled with the sudden arrangement of online education. With little time to plan for an emergency online transition, instructors seek out pedagogical tips through social media such as Facebook’s private “Pandemic Pedagogy” group (with 32,432 members). The once public Facebook group revealed surprising disparities across teaching pedagogies during a global pandemic. Colorful debates emerged between providing asynchronous versus synchronous lectures. Should final exams utilize online proctoring services? Are instructors expected to adapt academic expectations and/or provide emotional support to students? The aim of this chapter is to provide a thematic analysis of key debates highlighting the disparity in university remote teaching effectiveness during a pandemic.